Memfasilitasi kreativitas dan pemahaman konseptual dalam tugas botani tumbuhan tingkat rendah: persepsi mahasiswa tentang Canva - Yudhistian Yudhistian; Tabitha Sri Hartati Wulandari (Universitas Negeri Jakarta, 2026)
Understanding the multidimensional perceptions of ease-of-use, satisfaction, motivation, creative skills, and conceptual understanding is crucial for evaluating the effectiveness of the Canva platform in lower-plant botany courses. This study aims to describe students’ perceptions of ease-of-use, satisfaction, and motivation in using Canva, and to explore their impact on creativity skills and conceptual understanding in Canva-assisted lower-plant botany course assignments. The study design was mixed-methods research involving 40 subjects. The research instrument included 25 closed-ended and 10 open-ended questionnaires for data collection, which were analyzed using a mixed-methods approach. The analysis revealed that all five indicators were in the very high category, with the highest percentage recorded for creativity skills (90.1%) and the lowest for conceptual understanding (87.2%). The qualitative analysis also confirmed students’ positive responses to the five indicators. The study concluded that the majority of students experienced ease-of-use, satisfaction, and increased motivation when using Canva, which significantly enhanced their creativity and conceptual understanding when completing lower-plant botany assignments. It is recommended that future experimental studies utilize specific rubrics to evaluate the balance between visual creativity and conceptual accuracy.